Struggle for mastery : disfranchisement in the South, 1888-1908 - Perman, Michael (Fred W. Morrison series in Southern studies., 2001)
Around 1900, the Southern states embarked on a series of political campaigns aimed at disfranchising large numbers of voters. This volume presents a systematic study of the history of disfranchisement in the South, examining the origins, objectives and process of the movement.